Factors Influencing the Successful Adoption of Information Technology in High School Institutions in Indonesia - Setyadi, Resad (2024)
The COVID-19 pandemic has profoundly impacted the global community, compelling businesses across all sectors to adapt to advancements and trends in Information Technology (IT). The education sector, mainly High School Institutions (HSI), has experienced significant adaptation due to the pandemic. Stakeholders play a vital role in HSIs as they oversee and control IT decisions that can positively or negatively influence business outcomes. Therefore, HSI must establish an effective IT success implementation that guides decision making and ensures IT initiatives align with business value. This research aims to identify factors influencing IT Success () Adoption for HSI. The success of factors influencing IT Adoption are specifically tailored for HSIs in Indonesia. The HOP, BTH, DSC, and INS influence the QOI, QSY, and QSV. They all also affect the system trust variable. This study focuses on quantitative methods by sharing the questionnaire and interview. In this research, 400 respondents from 20 High School Institutions (HSIs) were selected as the sample for the study. SMART PLS analyzes the data starting from the validity of the questionnaire was assessed, and the results indicated that it is valid, as the Average Variance Extracted (AVE) test score was 0.756, which is higher than the recommended threshold of 0.5. The reliability of the questionnaire was also assessed. It was reliable, as the average Cronbach's alpha test score exceeded the threshold of 0.7. The analysis of the Bootstrapping technique revealed that all exogenous constructs collectively accounted for 81.4% of the impact. This indicates that the selected constructs have a significant influence. Further analysis of the Bootstrapping results revealed that seventeen direct effects significantly influenced, as their p-values were lower than 0.05. On the other hand, six direct effects were found to be not significant, as their p-values were higher than 0.05. These findings suggest that the selected constructs and their corresponding direct effects substantially influence HSIs. The research provides empirical evidence supporting the importance of these factors in shaping effective IT adoption in Successful practices. there were three research findings. Firstly, this research succeeded in knowing problems in the HSI sector in Indonesia. Secondly, the framework has been developed for HSI in Indonesia. Third, this framework can help to solve the IT Adoption problem at HSI in Indonesia. The recommendation of this thesis research is this study can influence the mindset of HSI stakeholders to consider IT Adoption implementation for the HSI Business value. The benefit after this research finishes is the stakeholders who are interested and consider to use this framework can implement this framework.